Perbandingan Darah Babi dan Lama Pembakaran terhadap Karakteristik â€œNasi Tokeâ€ Khas Riung, NTT - Yohanes Lewa; A.A. Made Semariyani; Ni Made Ayu Suardani Singapurwa (GEMA AGRO, 2019)
"Toke rice" is a typical food of Riung, East Nusa Tenggara. "Toke rice" is usually used to eat together at a traditional larik (caci) party or harvest celebration. "Toke rice" also becomes the main menu at the thanksgiving event at the beginning of every turn of the year. The "toke rice" ceremony is a ritual as an expression of gratitude for the harvest, as well as the life that has been spent for the past year. This ceremony is also an expression of protection and harmony for the life to come. The "toke rice" ceremony is usually performed at the start of farming or farming. This activity is a hereditary obligation, which must be carried out as an expression of gratitude, a gathering of extended family, as well as a blessing on the preservation of the surrounding nature. The purpose of this research is to find out how long it takes to burn the characteristics of "toke rice" and to find out the comparison of pig blood in making toke rice with good characteristics and preferred by consumers. This research uses factorial randomized block design (RBD) with 2 factors: The first factor is the amount of pig blood, which consists of 4 levels and the second factor is the burning time, consisting of 3 levels. Each treatment was repeated 2 times to obtain 24 combination treatments or experimental units. Observations made on "toke rice" products include objective and subjective observations. Objective observations include Moisture, Carbohydrate, Protein, Ash content, Fat content, pH, Subjective Observation covering aroma, taste, color, texture, overall acceptance. The best interaction treatment on objective and subjective observations was obtained from the treatment of adding 20% amount of pig blood and 45 minutes burning time, with characteristic water content of 51.068%, ash content of 1.173%, fat content of 8.591%, protein content of 11.818%, carbohydrate content of 33.217% and the degree of acidity (pH) 3,275, while from observations of color, taste, aroma, texture and overall inclusion received by the panelists with rather favorable assessment scores